Prime Minister Decree No. 1138/2013 Amending Prime Minister Decree No. 144/2013 On Establishing A Ministerial Committee For The Project Of The Development Of The Suez Canal Region = قرار رئيس مجلس الوزراء رقم 1138 لسنة 2013 بتعديل قرار رئيس مجلس الوزراء رقم 144 لسنة 2013 بتشكيل لجنة وزارية لمشروع تنمية إقليم قناة السويس - Egypt; The middle east library for economic services, translator. (2025)
Decree of the prime minister no. 1138 of the year 2013 قرار رئيس مجلس الوزراء رقم 1138 لسنة 2013